Cultivating a Sense of Place in Religious Studies - Jensen, Molly Hadley (Teaching theology and religion, 2015)
This essay analyzes student learning through place-based pedagogies in an American Religions course. In the course, students analyzed cultural meanings and practices of regional religious communities and participated in sensory awareness and ecological learning in a campus garden. Embodied learning increased student understanding and appreciation of land-based religious practices and epistemologies, and promoted multiple student literacies. In Religious Studies, place-based learning is vital to the examination of the rich dimensions and expressions of religious experience. Across disciplines, place-based pedagogies can expand and deepen text-based learning, cultivate recognition of various ways of knowing, foster affective connections to the local community, and develop critical skills for addressing patterns of displacement and ecological denigration.